Uji Kemampuan Pemangsaan Coccinella transversalis Fabricius. terhadap Aphis gossypii Glover. dan Bemisia tabaci Genn. Hama Tanaman Cabai Merah - Salbiah, Desita; Hidayat, wahyu - (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2023)
ABSTRACT Red chilli (Capsicum annuum L.) is a important commodity and has high economic value in Indonesia. Obstacles in cultivating red chilli are pest attacks, namely aphids (Aphis gossypii Glover) and whitefly (Bemisia tabaci Genn.). The use of predator (Coccinella transversalis Fabricius.) can be alternative to controlling A. gossypii and B. tabaci in a safe way. This research aims to know the ability of predator C. transversalis to prey nymph of A. gossypii and nymph of B. tabaci. This research was carried out at the Plant Pests Laboratory and Green House of the Faculty of Agriculture, Riau University which was carried out for three months from Maret to Mei 2022. The study was carried out experimentally using a completely randomized design (CRD), which consisted of six treatments and four replications. The treatments used was preying ability of the predator C. transversalis against A. gossypii and B. tabaci as prey. The results showed that the C. transversalis preferred the prey of the nymph A. gossypii compared to the prey of the nymph B. tabaci. Predator C. transversalis are able to prey on 46-48 A. gossypii nymphs per day and are able to prey on 43-44 B. tabaci nymphs per day. Preying ability of predator C. transversalis as biological agents with prey A. gossypii and B. tabaci between one male, one female and one pairs predator showed no difference in predation ability.Keywords : Coccinella transversalis Fabricius., Aphis gossypii Glover., Bemisia tabaci Genn., Preying ability